Tuning the Covering on Gold Surfaces by Grafting Amino-Aryl Films Functionalized with Fe(Ii) Phthalocyanine: Performance on the Electrocatalysis of Oxygen Reduction - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J; Silva-Molina, C; Silva-Molina, C; Gomez-San Martin, A; Gomez-San Martin, A; Agurto-Doren, N; Agurto-Doren, N; Olguín-Choupay, C; Olguín-Choupay, C; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Current selective modification methods, coupled with functionalization through organic or inorganic molecules, are crucial for designing and constructing custom-made molecular materials that act as electroactive interfaces. A versatile method for derivatizing surfaces is through an aryl diazonium salt reduction reaction (DSRR). A prominent feature of this strategy is that it can be carried out on various materials. Using the DSRR, we modified gold surface electrodes with 4aminebenzene from 4-nitrobenzenediazonium tetrafluoroborate (NBTF), regulating the deposited mass of the aryl film to achieve covering control on the electrode surface. We got different degrees of covering: monolayer, intermediate, and multilayer. Afterwards, the ArNO2 end groups were electrochemically reduced to ArNH2 and functionalized with Fe(II)-Phthalocyanine to study the catalytic performance for the oxygen reduction reaction (ORR). The thickness of the electrode covering determines its response in front of ORR. Interestingly, the experimental results showed that an intermediate covering film presents a better electrocatalytic response for ORR, driving the reaction by a four-electron pathway. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.